2013
DOI: 10.4291/wjgp.v4.i4.108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of occupational stress on the gastrointestinal tract

Abstract: The aim of this review is to provide a general overview of the relationship between occupational stress and gastrointestinal alterations. The International Labour Organization suggests occupational health includes psychological aspects to achieve mental well-being. However, the definition of health risks for an occupation includes biological, chemical, physical and ergonomic factors but does not address psychological stress or other affective disorders. Nevertheless, multiple investigations have studied occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 58 publications
1
65
0
6
Order By: Relevance
“…The autonomic nervous system, hypothalamic-pituitary axis, and genetic factors participate in gastrointestinal tract alterations in workers [12] moreover, change in the intestinal microbiota can interact with the immune and nervous systems leading to GIT symptoms [13]. In the present study continuous stress was commoner among participants with irritable bowel syndrome with significant statistical difference confirming the above observation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The autonomic nervous system, hypothalamic-pituitary axis, and genetic factors participate in gastrointestinal tract alterations in workers [12] moreover, change in the intestinal microbiota can interact with the immune and nervous systems leading to GIT symptoms [13]. In the present study continuous stress was commoner among participants with irritable bowel syndrome with significant statistical difference confirming the above observation.…”
Section: Discussionsupporting
confidence: 80%
“…Onset of pain related to a change in the frequency of stool 3. Onset of pain associated with a change in the form (appearance) of stool without any underlying systemic, organic or metabolic causes [12]. A structured questionnaire was used to collect sociodemographic factors, absence from work or sick leave due to IBS symptoms, partner employment, house type (own vs. rent), income, income adequacy, participation in care of children, continuous stress, excessive, and sleeping hours.…”
Section: Methodsmentioning
confidence: 99%
“…Empirical evidence collected over the past 50 years suggests that compared with other occupational groups, professional drivers tend to have a higher prevalence of cardiovascular [54,55], musculoskeletal [46], and gastrointestinal diseases [35]. Regarding with mental health problems, it was found that depression, anxiety, and post-traumatic stress disorders are highly prevalent in professional drivers, and are contributing factors for work-related accidents [6,8,54].…”
Section: Professional Drivers' Health and Road Safetymentioning
confidence: 99%
“…Burnout is associated with negative health outcomes such as anxiety [29], depression [29,30], sleep disturbances [31][32][33], headache [34], gastrointestinal disease [35], hypertension [36], muscle tension [34], and chronic fatigue [37], and especially in the case of professional drivers, with poor job performance [38,39]. Burnout is also associated with negative organizational outcomes such as absenteeism and high turnover intention [40,41].…”
Section: Burnout In the Field Of Professional Drivingmentioning
confidence: 99%
“…As working in the open air, sanitation workers are also suffered from rain, snow, sand, cold and ultraviolet rays. These factors lead to harmful effects on the overall health of the sanitation workers, including skin 2 , hair 3 , respiratory 4 , gastrointestinal 5 , urogenital 2 , as well as orthopedic problems 6 . Skin serves as a natural barrier from pathogens and damage between the internal and external environment in body defense, and is predisposed to disease when subjected to environmental stressors.…”
Section: Corresponding Authormentioning
confidence: 99%